Calculate the Inter-pressure of Multi-stage Compressors - Esber, Mouna Safi (Latakia University Journal -Engineering Sciences Series, 2020)
In this paper, the exponential equations with fractional indexes used in the calculation of inter-compressors and the relationship between absorption and expulsion pressures are replaced at known hypotheses by linear equations. The proposed method simplifies arithmetic work, and produces results with sufficiently high accuracy for practical design. يتم في هذا البحث استبدال جملة المعادلات الأسية ذات الدلائل الكسرية المستخدمة في حساب الضغوط البينية، وتحديد العلاقة بين ضغوط الامتصاص والطرد، وذلك عند فرضيات معروفة، وذلك باستخدام جملة معادلات خطية، والتي بمساعدتها يمكن تحديد قيم الضغوط البينية. الطريقة المقترحة تبسط العمل الحسابي، وتعطي نتائج ذات دقة عالية كافية من أجل التصميم العملي.